The effect of boron doping on the optical, morphological and structural properties of Cu3SbS3 thin films prepared via spin coating - Yagci, Ozlem; Yuksel, Sureyya Aydin; Bozkurt, Kutsal; Altindal, Ahmet (ROYAL SOC CHEMISTRY, 2023)
Copper antimony sulfide (Cu3SbS3) is considered a promising photovoltaic absorber material due to its abundance in soil, low cost and environmentally friendly constituents. However, production by methods that require high cost and abundant materials and the differences between the results obtained in the limited number of studies carried out limit the discovery of its photovoltaic performance. In this study, Cu3SbS3 thin films were produced for the first time using spin coating. Optical, morphological and structural characterization of the thin films produced using Cu and Sb in different ratios (0, 0.1, 0.3, 0.5 and 1) was investigated in order to determine the optimum Cu to Sb ratio to form the Cu3SbS3 phase. According to the results obtained, the Cu3SbS3 phase was formed at higher Cu/Sb ratios. In order to produce Cu3SbS3 thin films with improved optical and morphological properties, the film was doped with boron (B), for the first time, and its properties were tested. It was seen that boron doping significantly improved the properties of the Cu3SbS3 thin film. The obtained results showed that the boron doped Cu3SbS3 thin film with improved properties, which can be easily produced using low-cost methods and dopant materials, is a suitable candidate as an absorber layer for high-performance solar cells.
Keywords: CHEMICAL BATH DEPOSITION; SOLAR-CELL; CUSBS2; PRECURSORS; SB; Chemistry